A Systematic Review on Subjective Cognitive Complaints: Main Neurocognitive Domains, Myriad Assessment Tools, and New Approaches for Early Detection - Felipe Webster-Cordero; Lydia Giménez-Llort (Geriatrics)
Background/Objectives: Neuropsychological testing is key in defining cognitive profiles at early stages of dementia. More importantly, the detection of subtle cognitive changes, such as subjective cognitive complaints (SCCs), an understudied phenomenon, is critical for early detection and preventive interventions. Methods: This systematic review analyzes the empirical data on the cognitive domains and neuropsychological tests used in studies addressing SCC in the last 15 years (2009–2024). Results: A selection of 15 papers with exploratory, cross-sectional, and prospective scope in this field was obtained from PubMed and Embase databases. They used screening tests (17%) and a broad spectrum of neurocognitive domains. Yet, we identified three main targeted cognitive domains: executive functions (28%), language (17%), and memory (17%). Myriad assessment tools were also applied, but the most commonly used was a set of eight tests: Mini-mental Scale Examination (MMSE), Trail Making Test (A-B), Stroop test, Digit span test (DST), Semantic and Phonological fluency test, Rey Auditory Verbal Learning Test (RAVLT), Weschler Memory Scale (WMS), and Boston Naming Test (BNT). New approaches involved including the Geriatric Depression Scale (GDS) and self/informant reports. Conclusions: Despite scarce agreement in the assessment protocols, the identification of early neurocognitive symptoms to objectivate the SCC phenomenon envisions a broad field of research.